Cannabis (THC) Aggravates the Deleterious Effects of Alcohol (EtOH) on Skeletal Muscles’ Mitochondrial Respiration: Modulation by Age and Metabolic Phenotypes - Anne-Laure Charles; Margherita Giannini; Alain Meyer; Anne Charloux; Samy Talha; Thomas Vogel; Jean-Sébastien Raul; Valérie Wolff; Bernard Geny (Biology)
The anti-inflammatory and analgesic properties of cannabis might be useful to treat muscle diseases, including those linked or not to alcohol. Nevertheless, delta 9 tetrahydrocannabinol (THC) and ethanol (EtOH), often used concomitantly, can have deleterious effects on cardiac mitochondria. We therefore determined whether EtOH, alone and associated with THC, impairs skeletal muscle mitochondrial respiration. Further, we investigated potential modulation by metabolic phenotype and age by analyzing predominantly glycolytic gastrocnemius and oxidative soleus muscles in young and middle-aged rats (12 and 49 weeks). Considering the gastrocnemius, EtOH impaired mitochondrial respiration in a similar manner in young- and middle-aged muscles (−34.97 ± 2.97% vs. −37.50 ± 6.03% at 2.1 × 10−5 M; p < 0.05). Interestingly, concomitant THC aggravated EtOH-related mitochondrial impairment in young gastrocnemius (−49.92 ± 1.69%, vs. −34.97 ± 2.97 p < 0.05). Concerning the soleus, EtOH alone mainly decreased young muscle mitochondrial respiration (−42.39 ± 2.42% vs. −17.09 ± 7.61% at 2.1 × 10−5 M, p < 0.001, at 12 and 49 weeks). The soleus was less impaired at 12 weeks by THC and EtOH association than the gastrocnemius (−49.92 ±1.69 vs. −27.22 ± 8.96% in gastrocnemius and soleus, respectively, p < 0.05). In conclusion, EtOH, alone and associated with THC, significantly impairs skeletal muscle mitochondrial respiration and THC aggravates EtOH-induced effects on young glycolytic muscle. Age and metabolic phenotypes modulate these deleterious effects, with the glycolytic muscles of young rats being more prone to impairments than oxidative muscles.